The Role of Intrinsic Defects in Methylammonium Lead Iodide Perovskite - Kim, Jongseob; Lee, Sung-Hoon; Lee, Jung Hoon; Hong, Ki-Ha (American Chemical Society, 2014)
One of the major merits of CH3NH3PbI3 perovskite as an efficient absorber material for the photovoltaic cell is its long carrier lifetime. We investigate the role of the intrinsic defects of CH3NH3PbI3 on its outstanding photovoltaic properties using density-functional studies. Two types of defects are of interest, i.e., Schottky defects and Frenkel defects. Schottky defects, such as PbI2 and CH3NH3I vacancy, do not make a trap state, which can reduce carrier lifetime. Elemental defects like Pb, I, and CH3NH3 vacancies derived from Frenkel defects act as dopants, which explains the unintentional doping of methylammonium lead halides (MALHs). The absence of gap states from intrinsic defects of MALHs can be ascribed to the ionic bonding from organic inorganic hybridization. These results explain why the perovskite MALHs can be an efficient semiconductor, even when grown using simple solution processes. It also suggests that the n-/p-type can be efficiently manipulated by controlling growth processes.